TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG DAN KONSUMSI SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Yulyanah Yulyanah; Sri Yani Kusumastuti (Media Ekonomi, 2019)
This study aimed to examine the effect of profit level, debt level and institutional ownership to tax avoidance. The population in this study amounted to 18 food and beverage companies listed on the Indonesia Stock Exchange (BEI) in the period 2013-2017. Determination of the sample using purposive sampling method and obtained a sample of 5 food and beverage companies based on certain criteria. Independent variables used in this study profit level, debt level and institutional ownership, and the dependent variable was measured using the tax avoidance the measured of the book tax difference (BTD). The analysis tool used is the panel regression and the selected model is a fixed effect model. The result showed that profit level has positive effect on the tax avoidance. Meanwhile the debt level does not have effect on the tax avoidance and institutional ownership has negative effect on tax avoidance.